2016
DOI: 10.1128/aem.01177-16
|View full text |Cite
|
Sign up to set email alerts
|

A Small Number of Phylogenetically Distinct Clonal Complexes Dominate a Coastal Vibrio cholerae Population

Abstract: Vibrio cholerae is a ubiquitous aquatic microbe in temperate and tropical coastal areas. It is a diverse species, with many isolates that are harmless to humans, while others are highly pathogenic. Most notable among them are strains belonging to the pandemic O1/O139 serogroup lineage, which contains the causative agents of cholera. The environmental selective regimes that led to this diversity are key to understanding how pathogens evolve in environmental reservoirs. A local population of V. cholerae and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 62 publications
(76 reference statements)
0
42
1
Order By: Relevance
“…Non-O1/non-O139 V. cholerae serogroups are also linked to V. cholerae gastroenteritis as well as to wound infections and bacteremia (Deshayes et al, 2015 ). V. cholerae O1, O139 and non-O1/O139 comprise a single taxonomic species and their habitats attributes are similar (Lewin, 1996 ), however, recently it has been suggested that not all strains of V. cholerae species share the same niche (Kirchberger et al, 2016 ). The role of CT in the environment is not understood.…”
Section: Introductionmentioning
confidence: 99%
“…Non-O1/non-O139 V. cholerae serogroups are also linked to V. cholerae gastroenteritis as well as to wound infections and bacteremia (Deshayes et al, 2015 ). V. cholerae O1, O139 and non-O1/O139 comprise a single taxonomic species and their habitats attributes are similar (Lewin, 1996 ), however, recently it has been suggested that not all strains of V. cholerae species share the same niche (Kirchberger et al, 2016 ). The role of CT in the environment is not understood.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous mostly harmless lineages of Vibrio coexist within niches, competing for largely similar resources2. Among them are a few human pathogens of relevance, including Vibrio cholerae, the causative agent of the sometimes dramatic and lethal cholera diarrhea.…”
mentioning
confidence: 99%
“…Nucleotide analysis confirmed that all strains were Vibrio isolates using a criteria with a 99%–100% query coverage and an E ‐value of 0. The hsp60 locus was chosen for phylogenetic analysis since it has previously been used to characterize the population‐level diversity of vibrios and provides a robust and more defined tree structure compared to the 16S rRNA gene (Cordero, Wildschutte, et al., ; Hunt et al., ; Kirchberger et al., ; Preheim et al., ). From phylogenetic results, we identified that 40 of the 102 strains were unique at hsp60 nucleotide sequence.…”
Section: Resultsmentioning
confidence: 99%